Voices of Wisdom: The Portuguese Example of José Leite de Vasconcellos - Soares, Marinela; Soares, Rui (Tautosakos darbai, 2026)
Marking memories from decades and decades is giving voice to proverbial wisdom at a local, regional, national and international level. During this time, continued activities in the field of paremiology were defined with a desire for rapprochement between generations, based on the maturity of concepts and the creativity that this theme involves. This article aims to demonstrate how individuals dedicated to preserving cultural heritage by documenting customs, habits and cultural experiences contribute to their preservation and help reveal and comprehend the national worldview. It focuses primarily on the work of the Portuguese philologist, archaeologist and ethnographer José Leite de Vasconcellos (1858–1941). As well as his contributions to linguistics, ethnography, and paremiology his work was characterised by a profound national consciousness, as he applied the achievements of universal science to the Portuguese countryside. This opened up new perspectives for science in Portugal. Just like other figures of that time, the works of Vasconcellos show that understanding, disseminating and applying the wisdom of people contributes to the construction of a fairer and more balanced society, bridging the duality between the empirical and the scientific. With commitment and guidance, traditional paremiological concepts can be disseminated and realised, based on the hope of a favourable outcome, as Kazys Grigas did.